PERANAN PENDIDIKAN AGAMA ISLAM DALAM PENGUATAN NASIONALISME DI INDONESIA - Abdul Hamid (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2018)
Abstract The 21st century is a triumph for the era of globalization. An era that tries to make the world, especially the world incorporated in the third world category (developed) like Indonesia to carefully and firmly address all the effects it produces. Globalization is, in essence, a process of generating ideas, then offered to be followed by other nations that eventually arrive at a common point of agreement and serve as a common ground for nations around the world. Globalization as well as nationalism is a concept of a pluralistic. Substantively also contains a contradictory spirit. Nationalism with the spirit of exclusiveness desires loyalty to the nation and state. Nationalism, in any way, tried to convince a nation that felt the same ground, breathed the same air, and drank water from the same source, that is, Bumi Indonesia. To love the homeland that gives the source of life as a gift of Allah SWT. So that every form of natural produce should be utilized as well as possible for the common welfare as a nation. In the process, Indonesia tries to shed tribal, religious, racial and linguistic identity for a cooperation to achieve prosperity. While Islam is one of the religions that desires the unity and unity among human beings. Encourage his people to love and work for the inhabited country. Abstrak Abad 21 merupakan masa kejayaan bagi era globalisasi. Sebuah era yang mencoba menjadikan dunia, khususnya dunia yang tergabung dalam kategori dunia ketiga (berkembang) seperti Indonesia untuk secara cermat dan tegas menyikapi segala efek yang ditimbulkannya. Globalisasi pada hakikatnya adalah suatu proses dari gagasan yang dimunculkan, kemudian ditawarkan untuk diikuti oleh bangsa lain yang akhirnya sampai pada suatu titik kesepakatan bersama dan menjadi pedoman bersama bagi bangsa-bangsa di seluruh dunia. Globalisasi sebagaimana juga nasionalisme adalah sebuah konsep berwajah majemuk. Secara substansif juga mengandung semangat yang bertolak belakang. Nasionalisme dengan semangat eksklusifisme menghendaki kesetiaan kepada bangsa dan negara. Nasionalisme, dalam rupa apapun sejatinya mencoba meyakinkan bangsa yang merasa berpijak pada bumi yang sama, menghirup udara yang sama, juga meneguk air dari sumber yang sama, yakni Bumi Indonesia. Untuk mencintai tanah airnya yang memberikan sumber kehidupan sebagai anugerah Allah SWT. Sehingga setiap wujud hasil alam harus dimanfaatkan dengan sebaik-baiknya untuk kesejahteraan bersama sebagai suatu bangsa. Dalam prosesnya, Indonesia mencoba menanggalkan identitas kesukuan, agama, ras maupun bahasa demi sebuah kerjasama mencapai kesejahteraan. Sementara Islam adalah salah satu agama yang sangat menghendaki adanya persatuan dan kesatuan antar umat manusia. Menganjurkan umatnya untuk mencintai dan bekerja untuk negeri yang didiami. Kata Kunci: